A modified artificial bee colony algorithm for order acceptance in two-machine flow shops - Wang, Xiuli; Xie, Xingzi; Cheng, T.C.E. (International journal of production economics, 2013)
We consider a two-stage make-to-order production system characterized by limited production capacity and tight order due dates. We want to make joint decisions on order acceptance and scheduling to maximize the total net revenue. The problem is computationally intractable. In view of the fact that artificial bee colony algorithm has been shown to be an effective evolutionary algorithm to handle combinatorial optimization problems, we first conduct a pilot study of applying the basic artificial bee colony algorithm to treat our problem. Based on the results of the pilot study and the problem characteristics, we develop a modified artificial bee colony algorithm. The experimental results show that the modified artificial bee colony algorithm is able to generate good solutions for large-scale problem instances. ► We consider order acceptance in two-machine flow shops. ► The net revenue of an accepted order is its revenue minus its weighted tardiness. ► The objective is to maximize the total net revenue. ► We propose a modified artificial bee colony algorithm which is able to solve large-scale problem instances effectively.